Perlindungan Hukum terhadap Pekerja yang Bekerja Melebihi Waktu Kerja (Studi Pada Perusahaan UD. Indra Jaya Seafood Supplier) - Ayu Adi Ulansari (Jurnal Preferensi Hukum, 2020)
Work that is done outside working hours is something that is outside the obligations of the workers. This study aims to analyze the implementation of legal protection for workers who work outside of working time at the UD company. Indra Jaya Seafood Supplier, as well as inhibiting factors in the application of legal protection to workers who work beyond the working time limit at UD company. Indra Jaya Seafood Supplier. This type of research used in this research is empirical legal research. The results showed that the company UD. Indra Jaya Seafood Supplier in hiring more workers than the time stipulated by law. The reason is, if you add up, sometimes companies are expected to employ workers more than 14 hours a week. Regarding the obligations of employers to workers who exceed working hours, UD company. Indra Jaya Seafood Supplier has done it optimally in accordance with the prevailing laws and regulations. This is because workers who work outside working hours at the company have been asked for prior approval, are given overtime pay, are given adequate rest time, and provide food and drinks. The inhibiting factor in the application of legal protection for workers who exceed working hours at UD company. Indra Jaya Seafood Supplier, namely the demands of consumers to deliver goods on time (deadline), less than optimal performance of workers in preparing goods for delivery, and also a lack of manpower currently.